CIVILIZATION OF YOUTH IN THE DEVELOPMENT OF CIVIL SOCIETY ISSUES OF INCREASING ACTIVITY - Orinbetov, N.T. (SCIENCE and SOCIETY, 2026)
The article analyzes the theoretical and practical aspects of enhancing youth civic engagement in the process of developing civil society. It highlights the participation of young people in socio-political processes and examines the factors influencing the formation of civic awareness and responsibility. The mechanisms of cooperation between youth and civil society institutions are also discussed. The paper proposes recommendations aimed at addressing existing challenges.